1996
DOI: 10.1080/02652039609374469
|View full text |Cite
|
Sign up to set email alerts
|

Determination of hydrolysed fumonisin B1in alkali‐processed corn foods

Abstract: Treatment of fumonisin B1 (FB1)-contaminated corn with calcium hydroxide solution is known to cause large losses of FB1 and formation of the aminopentol AP1 by hydrolysis. Methodology was developed for determination of AP1 in foods manufactured from calcium hydroxide-processed corn. The ground food (tortilla chips, nacho chips, taco shells, or air-dried corn tortillas) was extracted with methanol-water (8:2) or methanol-acetonitrile-water (25:25:50), which also extracted FB1 and fumonisin B2 (FB2). Clean-up fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 25 publications
1
50
2
Order By: Relevance
“…However, the resulting products, when strong alkaline solutions are used, are still regarded as toxic compounds (Murphy et al, 1996). Scott and Lawrence (1996) and Sydenham et al (1995) found a ratio for FB1 to AP1 nd: not detected. a Parenthesis indicate importing country.…”
Section: Alkaline Solutionsmentioning
confidence: 90%
“…However, the resulting products, when strong alkaline solutions are used, are still regarded as toxic compounds (Murphy et al, 1996). Scott and Lawrence (1996) and Sydenham et al (1995) found a ratio for FB1 to AP1 nd: not detected. a Parenthesis indicate importing country.…”
Section: Alkaline Solutionsmentioning
confidence: 90%
“…The suppression of the derivatization reaction by the metal ions could be avoided by the addition of ethylenediaminetetraacetic acid (EDTA) to the reaction medium (Miyano et al, 1985a). The derivatization using NBD-F as a pre-column fluorogenic reagent was applied to the determination of amino acids Imai et al, 1982;Imai, 1983, 1984;Kotaniguchi et al, 1987), amines, amino acids and imino acids , amines and proteins (Miyano et al, 1985b), hexosamines and hexosaminols (Imanari et al, 1985), neutral sugars as their glycamines (Shinomiya et al, 1987), aminophospholipids (Kaneko et al, 1987), Ssulfocysteine and S-sulfoglutathione (Togawa et al, 1988), phosphatidylethanolamine and its lysoform (Saris and Somerharju, 1989), amphetamine-related compounds (Hayakawa et al, 1989), selenium (Nakagawa et al, 1989), cyclamate (Hauck and Köbler, 1990), penicillins (Iwaki et al, 1990), ammonia (Kobayashi et al, 1992), peptides Arg-Gly-NH 2 and Arg-Pro-Lys-Pro (Yoshinaga et al, 1994), cholinergic channel activator A82695 (Hui and Marsh, 1995), dipeptides (Beijersten and Westerlund, 1995), hydrolyzed fumonisin B 1 (Scott and Lawrence, 1996), anatoxin-a (James and Sherlock, 1996;James et al, 1997), proteines (Wise et al, 1996), peptides (Kanazawa et al, 1997) (Jiménez and Mateo, 1997), anatoxin-a, homoanatoxin-a and their degradation products (James et al, 1998), methamphetamine and related compounds , imine-linked opines (Zhang et al, 1998), L-arginine (Prados et al, 1999), D-penicillamine (Al-Majed, 2000) and neurotoxin domic acid (James et al, 2000). Furthermore, after the derivatization with NBD-F, the enantioselective separation of amino acids were achieved on the chiral stationary phases ...…”
Section: Reagentsmentioning
confidence: 99%
“…Human exposure to fumonisins is therefore to be expected, especially in areas where nixtamalized maize is a diet staple. Surveys conducted on nixtamalized products originating from Mexico indicated that fumonisin levels were up to 1.8 mg/kg (De Girolamo, Pascale, & Visconti, 2011;Dombrink-Kurtzman & Dvorak, 1999;Scott & Lawrence, 1996).…”
Section: Introductionmentioning
confidence: 99%